THERAPEUTIC OPTIONS FOR PATIENTS WHO ARE NOT ELIGIBLE FOR INTENSIVE CHEMOTHERAPY - Elihu Estey (Mediterranean Journal of Hematology and Infectious Diseases, 2013)
Although “less intense” therapies are finding more use in AML, the principal problem in AML remains lack of efficacy rather than toxicity. Hence less intense therapies are of little use if they are not more effective as well as less toxic than standard therapies.. Assignment of patients to less intense therapies should be based on other factors in addition to age. Azacitidine and decitabine, the most commonly used less intense therapies in AML very probably produce better OS than best “supportive care” or “low-dose” ara-C. However improvement is relatively small when compared to expected life expectancy in the absence of disease. Accordingly, while azacitidine or decitabine should be considered the standards against which newer therapies are compared, continued investigation of potentially more effective therapies needs to continue. Better means for evaluating the large number of these therapies (and their combinations) are also needed.